2021
DOI: 10.1111/psyg.12674
|View full text |Cite
|
Sign up to set email alerts
|

Autoregressive cross‐lagged modelling of the relationship between social activity, depressive symptoms, and cognitive function in Korean elderly

Abstract: Background This study aimed to verify the reciprocal relationship between social activity, depressive symptoms, and cognitive function in Korean elderly, utilizing data from the Korean Longitudinal Study of Aging (conducted by the Korea Employment Information Service biennially from 2006 to 2018). Methods The data of 5549 people aged 60 and over (mean age 70.27 years, standard deviation = 7.26) were used in the final analysis. Autoregressive cross‐lagged analysis was used to examine bidirectional relationships… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 32 publications
3
9
0
Order By: Relevance
“…Our results strengthened the evidence of the cross-lagged effect of social activities on cognitive function found in a previous study, which used the same panel data (i.e., KloSA; Bae, 2021). Furthermore, we found that social participation had effects on cognitive function even after controlling for unmeasured time-invariant variables.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…Our results strengthened the evidence of the cross-lagged effect of social activities on cognitive function found in a previous study, which used the same panel data (i.e., KloSA; Bae, 2021). Furthermore, we found that social participation had effects on cognitive function even after controlling for unmeasured time-invariant variables.…”
Section: Discussionsupporting
confidence: 90%
“…Furthermore, we found that social participation had effects on cognitive function even after controlling for unmeasured time-invariant variables. In addition, the effect of social participation as a protective factor for the cognitive decline was confirmed in this study, the main difference being that the participants in this study had a mean age of 58.81 ± 9.09 years and were younger than those in a previous study (mean age, 70.27 ± 7.26 years;Bae, 2021).…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Preventing DS is an important prerequisite for improving the quality of life, especially for middle-aged and senior citizens. Published studies indicated that SE was closely related to DS and could act as a key factor in the prevention of DS (Solomonov et al, 2019 ; Bae, 2021 ). Results of previously published studies indicated that there were differences in the preventive effects of SE on depression in people with different characteristics (Min et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Since SE is associated with a low risk of DS, promotion of SE can provide a protective effect of preventing and mitigating the initiation and progression of DS at the lowest cost (Solomonov et al, 2019 ; Bae, 2021 ). However, as the studies mentioned above, the effect of SE is not homogenous for all subgroups of people.…”
Section: Introductionmentioning
confidence: 99%